Child welfare : Historical dimensions, contemporary debate - Hendrick, Harry (Book collections on Project MUSE., 2003)
This book offers a provocative account of contemporary policies on child welfare and the ideological thrust behind them and provides an informed historical perspective on the evolution of child welfare during the last century.